2022
DOI: 10.1039/d1ta09998a
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterisation of BaZr0.8Y0.2O3−δproton conductor densified at 1200 °C

Abstract: Barium zirconate-based perovskites (BZY) are intensely studied proton conductors for high-temperature electrochemical applications; however, their refractory nature means excessive temperatures are required for sintering (~1700 °C). Although, different strategies have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Proton-conducting oxides, which serve as electrolytes, are one of the main components in PCFCs. Among the reported proton-conducting oxides, yttrium-doped barium zirconate (BZY) has been widely investigated because of its high bulk proton conductivity and superior chemical stability. The protons can be introduced in BZY by the hydration reaction, as shown in the following: normalH 2 normalO + normalV normalO + normalO normalO × 2 OH normalO where V O •• , O O × , and OH O • are the oxygen vacancy, lattice oxygen, and hydroxide defect, separately …”
Section: Introductionmentioning
confidence: 99%
“…Proton-conducting oxides, which serve as electrolytes, are one of the main components in PCFCs. Among the reported proton-conducting oxides, yttrium-doped barium zirconate (BZY) has been widely investigated because of its high bulk proton conductivity and superior chemical stability. The protons can be introduced in BZY by the hydration reaction, as shown in the following: normalH 2 normalO + normalV normalO + normalO normalO × 2 OH normalO where V O •• , O O × , and OH O • are the oxygen vacancy, lattice oxygen, and hydroxide defect, separately …”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical investigations led to the conclusion that Y doped BZO may be a very promising electrolyte [2][3][4][5][6][7][8][9][10][11][12][13]. However, it was found experimentally that the thermodynamic stability of Y doped BZO decreases with increasing Y concentration [14][15][16][17][18][19][20][21]. Moreover, substitution of Y on Ba-or Zr-site may vary the electronic properties by a large extent, because of the ionic radii mismatch and different electron valence state of Y compared to Ba and Zr.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, substitution of Y on Ba-or Zr-site may vary the electronic properties by a large extent, because of the ionic radii mismatch and different electron valence state of Y compared to Ba and Zr. By using several experimental techniques, site occupation of Y and the corresponding synthesis conditions were discussed explicitly [15][16][17]. It was found that Y on Ba site increases the Ba deficiency [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Research focus has gradually shifted from zirconates to cerates due to enhanced conductivity and favorable sinterability. [16][17][18][19][20][21] Undoped barium zirconates or cerates have limited conductivity because proton conduction requires the creation of protonic defects in the ABO 3 perovskite lattice through dissociative adsorption of water (Reaction 1). In order to obtain sufficient proton conductivity under humidified conditions, it is necessary to introduce extrinsic oxygen vacancies by doping to allow for the incorporation of water, and acceptor-doping is the most commonly adopted strategy.…”
Section: Introductionmentioning
confidence: 99%